2022
DOI: 10.1002/bit.28301
|View full text |Cite
|
Sign up to set email alerts
|

3D‐printed PLA/Gel hybrid in liver tissue engineering: Effects of architecture on biological functions

Abstract: The liver is one of the vital organs in the body, and the gold standard of treatment for liver function impairment is liver transplantation, which poses many challenges.The specific three-dimensional (3D) structure of liver, which significantly impacts the growth and function of its cells, has made biofabrication with the 3D printing of scaffolds suitable for this approach. In this study, to investigate the effect of scaffold geometry on the performance of HepG2 cells, poly-lactic acid (PLA) polymer was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(96 reference statements)
0
3
0
1
Order By: Relevance
“…Rajalekshmi et al 36 reported that a fibrin-incorporated alginate dialdehyde–gelatin hydrogel has the potential to be used as a scaffold for liver tissue engineering using HepG2 cells. Moreover, Mirdamadi et al 37 reported that a 3D-printed poly-lactic acid (PLA)/Gel hybrid has architectural effects on biological functions in HepG2 cells. Thus, we used HepG2 cells as a model when initially evaluating the correlation between gel stiffness and hepatocyte functionality and establishing a 3D culture system.…”
Section: Resultsmentioning
confidence: 99%
“…Rajalekshmi et al 36 reported that a fibrin-incorporated alginate dialdehyde–gelatin hydrogel has the potential to be used as a scaffold for liver tissue engineering using HepG2 cells. Moreover, Mirdamadi et al 37 reported that a 3D-printed poly-lactic acid (PLA)/Gel hybrid has architectural effects on biological functions in HepG2 cells. Thus, we used HepG2 cells as a model when initially evaluating the correlation between gel stiffness and hepatocyte functionality and establishing a 3D culture system.…”
Section: Resultsmentioning
confidence: 99%
“…After 7 days of culture, the AD-MSCs/DPS constructs were gently washed with PBS, fixed with 2.5% glutaraldehyde, and then dehydrated in a graded ethanol series. The AD-MSCs/DPS was sputter-coated with a thin layer of gold and then analyzed under SEM (AIS2100; Seron Technologies, South Korea) …”
Section: Methodsmentioning
confidence: 99%
“…The AD-MSCs/DPS was sputtercoated with a thin layer of gold and then analyzed under SEM (AIS2100; Seron Technologies, South Korea). 54 2.4.4. H&E Staining.…”
Section: Acsmentioning
confidence: 99%
“…Una de las aplicaciones más vanguardistas del PLA es en el campo de la impresión 3D, donde tienen especial interés los materiales con memoria de forma para aplicaciones en biomedicina y tecnología celular [150]. La bioimpresión es una tecnología muy novedosa en la cual se está estudiando el desarrollo de órganos artificiales y tejidos en diferentes sistemas del organismo, como por ejemplo hígados o riñones [151]. El PLA ha sido utilizado mediante esta técnica para imprimir tejidos iniciales que luego son incubados y convertidos en órganos completos.…”
Section: I44 Aplicaciones Del Plaunclassified